Następstwa cykliczności płciowej kobiet a ważność testamentów samobójczyń - Mazurkiewicz, Jan (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The Polish Civil code legitimates that a will „is invalid, when it has been made […] in a condition which eliminate the conscious or unhampered making the decision”. It is worth to notice, that about 25% of women, who commits the suicide do that, during lasting usually 4 days, menstruation, which takes only part of 28-days menstrual cycle. Thus appears few questions: why so many women commit suicides exactly during the menstruation, when it takes only about 15% of the cycle, is there an influence of menstruation on the decision of taking one’s own life, and how much other circumstances have a relationship with that. Also, the most important, whereas the will made before the death, remembering the influence of all, very numerous factors which can enters the psyche, is valid according to Civil code
Keywords: civil code; invalidity of the will; suicide, menstrual cycle, menstruation, psyche